Peripheral giant cell granuloma associated with a dental implant - Rafaela Carriço Porto Baesso; Maria Carolina de Lima Jacy Monteiro Barki; Rebeca de Souza Azevedo; Karla Bianca Fernandes da Costa Fontes; Débora Lima Pereira; Renata Tucci; Fábio Ramôa Pires; Bruna Lavinas Sayed Picciani (BMC, 2019)
Abstract Background Peripheral giant cell granuloma (PGCG) is an uncommon pathology that affects gingival or alveolar mucosa. Although PGCG can be associated with dental implants, little is known about this lesion and implant osseointegration as well as its etiopathogenesis and the treatments available. This study sought to report a rare case of PGCG associated with dental implant, emphasizing its clinical and histopathological aspects. Case presentation A 53-year-old man had an exophytic, reddish lesion, around a crown attached to a dental implant located in the left mandible. Radiographically, there was bone loss around the implant. After excisional biopsy, histological examination revealed a submucosal proliferation of multinucleated giant cells rendering the diagnosis of peripheral giant cell granuloma. Patient has been under follow-up for 6 months with no recurrence. Conclusions Peri-implant lesions must be completely removed to prevent recurrence of PGCG and implant failure, even in cases suspected to be reactive. Besides, histological examination must be performed on all peri-implant reactions to achieve the appropriate diagnosis and, consequently, the best treatment and follow up.